Adsorption method for the remediation of brilliant green dye using halloysite nanotube - Ukkund, Shareefraza J. (2022)
Funding Information: The Deanship of Scientific Research at King Khalid University General Research Project under the grant number (R.G.P.2/138/42) and Taif University researchers supporting project number (TURSP–2020/157), Taif University, Taif, Saudi Arabia. Publisher Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland.